2013
DOI: 10.1890/12-0890.1
|View full text |Cite
|
Sign up to set email alerts
|

Competition and facilitation between a native and a domestic herbivore: trade‐offs between forage quantity and quality

Abstract: Potential competition between native and domestic herbivores is a major consideration influencing the management and conservation of native herbivores in rangeland ecosystems. In grasslands of the North American Great Plains, black-tailed prairie dogs (Cynomys ludovicianus) are widely viewed as competitors with cattle but are also important for biodiversity conservation due to their role in creating habitat for other native species. We examined spatiotemporal variation in prairie dog effects on growing-season … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 56 publications
4
35
0
Order By: Relevance
“…These patterns probably resulted from prairie dog activities during the grass growing season that enhance forage quality, such as removal of standing dead biomass and clipping of vegetation that increases plant nitrogen uptake, in addition to the lack of other more palatable forage options during the winter season [20,52]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patterns probably resulted from prairie dog activities during the grass growing season that enhance forage quality, such as removal of standing dead biomass and clipping of vegetation that increases plant nitrogen uptake, in addition to the lack of other more palatable forage options during the winter season [20,52]. …”
Section: Discussionmentioning
confidence: 99%
“…However, these ecological relationships between cattle and prairie dogs probably vary across the geographic ranges and different species of prairie dogs, and with variation in precipitation and plant productivity [52]. For example, in the mixed-grass prairie, cattle spend significantly more time in pastures with prairie dog colonies compared to pastures without colonies [39].…”
Section: Discussionmentioning
confidence: 99%
“…Repeated grazing is often necessary for maintaining high levels of secondary compounds (Gustafson and Ryan 1976), because the responses of food quality to grazing may be delayed (Saetnan et al 2012). The response of forage nitrogen content and digestibility in plants to grazing may be positive (Augustine and Springer 2013) or neutral (Saetnan et al 2012). In our study, MG in August showed a positive effect on crude protein.…”
Section: Discussionmentioning
confidence: 45%
“…The food competition hypothesis has been proposed to explain population declines of small rodents under livestock grazing pressure in other studies (Augustine and Springer 2013). Consistent with this hypothesis, decreased forage quantity, reflected in lower plant cover and height, have been widely reported in grazed sites (Steen et al 2005;Torre et al 2007).…”
Section: Discussionmentioning
confidence: 61%
“…Cattle and bison exhibit considerable dietary overlap (Plumb andDodd 1993, Hartnett et al 2007) and therefore above relatively low population levels we expect their relationship to be competitive. Effects of prairie dogs on livestock production are complex and, depending on site conditions such as rainfall amounts, may be facilitative or competitive (Derner et al 2006, Augustine andSpringer 2013). When competitive, the cost of prairie dog control may exceed reduced revenues from livestock production (Breland et al n.d.).…”
Section: Economic Trade-offs Between Lcm and Bcmmentioning
confidence: 99%